Case Study for a Palm Biomass Biorefinery Utilizing Renewable Sufars from Oil Palm Frond for the Production of Poly(3-hydroxybutyrate) Bioplastic - Mior Ahmad Khushairi, Mohd Zahari; Mohd Noriznan, Mokhtar; Hidayah, Ariffin; Shirai, Yoshihito; Mohd Ali, Hassan (2014)
In this paper, we assess the economic viability of renewable sugars from oil palm frond (OPF) as fermentation feedstock for the production of the bioplastic poly(3-hydroxybutyrate), P(3HB) within an integrated palm biomass biorefinery.